Head Spear Gun Injury: An Atypical Suicide Attempt. Issue 6 (September 2015) - Bakhos, David; Villeneuve, Alexandre; Kim, Soo; Lebrun, Helene; Dufour, Xavier
Abstract : Abstract: Weapon injuries with spear gun are rare. The aim of this case report is to report the emergency and surgical management when this event occurs. A 35-year-old man attempted suicide with a spear gun. The entry of the shaft was localized through the submental area without an obvious exit point. The projectile passed through the tongue and palatal bone. A tracheotomy was performed. Preoperative cranial computed tomography (CT) showed the harpoon was gone upward through the submental area, the oral cavity, the ethmoid paranasal sinus, the cribriform plate, and the frontal region without vessel damages. Under general anesthesia, the harpoon was pulled out in order to extract the shaft tip and the articulated wishbone. Osteo-meningeal defect of the ethmoid roof was closed using a middle turbinate flap. There were no neurologic deficit and no cerebro-spinal rhinorrhea at his 3-year follow-up visit. The trajectory of the shaft is different between attempted suicide and accident. Cranial CT scan is helpful to show the trajectory of the shaft. Angiogram can be helpful to see the relations between the tip shaft and the vessels. The knowledge of the shaft tip and the imagery findings are important to decide the best surgical approach.